Finance and Development, March 1980. (Finance and Development; Finance and Development ;, 1980)
This paper highlights that the flow of IMF-related resources to member countries was maintained at a high level during 1979, amounting to the equivalent of SDR 6,917 million, compared with SDR 4,955 million in 1978. Some SDR 3.77 billion became available to non-oil developing countries in 1979. Repurchases in the General Resources Account by all members-at SDR 4.2 billion-exceeded their purchases of SDR 1.8 billion by an unprecedented SDR 2.4 billion. These large repurchases reflected the substantial improvement in the balance of payments of some industrial member countries that had large outstanding drawings.